Hermeneutika Filosofis Hans-Georg Gadamer sebagai Basis Ontologis Multikulturalisme - mukalam mukalam; Siti Murtiningsih (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
AbstractThis paper aims to make Gadamer's philosophical hermeneutics the ontological basis of multiculturalism. This is interesting to do because, first, multiculturalism can be seen as a hermeneutical phenomenon and secondly, philosophical hermeneutics contains significant concepts for multiculturalism, such as tradition, effective historical awareness, dialogue and fusion of horizons. To reveal the ontological vision contained in philosophical hermeneutics, this paper uses Heidegger's existential ontology as its formal object, namely the concept of being-in-a-world. With analogical analysis, the ontological vision of philosophical hermeneutics is obtained, namely dialectical ontology. This ontological vision becomes the ontological basis for multiculturalism as dialogical multiculturalism.Â Keywords: Philosophical hermeneutics, ontology, multiculturalism